Exchange-coupled of soft and hard magnetic phases on the interfaces of Fe3C/CoFe2O4 nanocomposites. Issue 1 (January 2020) - Ye, Zhantong; Qie, Yaqin; Fan, Zhipeng; Liu, Yixuan; Yang, Hua
Abstract: It is extremely important and challenging to develop exchange-coupled nanomagnets with soft/hard magnetic phase to apply for energy-related devices. Herein, we presented a simple strategy to synthesize the Fe3 C/CoFe2 O4 nanocomposites by a chemical coprecipitation method, in which effective exchange coupling at hard and soft magnetic interfaces was achieved. The as-synthesized Fe3 C/CoFe2 O4 nanocomposites show exceptional exchange-coupled effect and enhanced magnetic properties. Moreover, this work provides a new soft magnetic phase and an entirely new attempt for nanomagnets based on soft/hard magnetic exchange coupling. Graphical abstract: The Fe3 C/CoFe2 O4 nanocomposites were prepared by chemical coprecipitation method, which show exceptional exchange-coupled effect and enhanced magnetic properties. This work provides a new soft magnetic phase and an entirely new attempt for nanomagnets based on soft/hard magnetic exchange coupling. Image 1